PENYULUHAN DONGENG SIRAH NABAWIYAH UNTUK MENINGKATKAN STIMULASI PENDIDIKAN KARAKTER RELIGIUS ANAK USIA DINI - Andri Nirwana AN; Abdullah Mahmud; Yuli Rohmiyati; Nunung Suryana Jamin; Ubaidillah (Yayasan Baitul Hikmah al-Zain, 2025)
The purpose of this writing is to find out the existence of the sirah nabawiyah fairy tale as a stimulation of religious character education for early childhood. The exploration of inspirational stories will emphasize more on the period before the revelation of the prophet, so that it can minimize the reasons for the inability of mankind to make Muhammad a role model and inspirational figure. This community service is motivated by the development of the era that continues to develop from time to time. Based on that, it is necessary to provide stimulation in terms of strengthening so that children have religious character education through the Sirah Nabawiyah fairy tale. The purpose of this community service is so that children can get to know the Prophet Muhammad and emulate the fairy tale that has been told to children. In addition, so that children have good character education and are based on the characteristics of the Prophet Muhammad. The target participants in this community service are children aged 5-6 years. The results of this community service show that children are very enthusiastic in following the fairy tales that are told and are enthusiastic. The activities carried out with direct practice are by reading the Sirah Nabawiyah fairy tale directly to children to make it easier for children to understand the fairy tale. It is hoped that through the Sirah Nabawiyah fairy tale for early childhood, it will be able to stimulate children's religious character education, so that the goal of stimulation will be achieved optimally.